PREPARING STUDENTS TO DEVELOP PEDAGOGICAL INDEPENDENCE (Universal International Scientific Journal, 2026)
The article highlights the importance of modern approaches and techniques in thedevelopment of cognitive independence of students. Intensification of informatization processes,providing students with educational materials through colorful pictures and graphics, helps to increasemotivation and develop cognitive independence. Educational reforms, while increasing the demand forqualified personnel and professionals, help to strengthen students ' interest and motivation for classes.Through the creation of problem situations, creativity and discussion, the need to develop students 'activity and independent thinking skills is emphasized. Cognitive independence, which involvesindependent activities and aspirations in the learning process, is also indicated to be developed throughpedagogical techniques and approaches
Keywords: cognitive independence; informatization processes; student motivation